Respostas
respondido por:
0
x²-8x+7=0
delta = b²-4ac
delta = (-8)² - 4 x 1 x 7
delta = 64 - 28
delta = 36
raiz de delta = 6
substituindo na fórmula de báskara: x = 8 + 6 / 2 ou x = 8 - 6 / 2
então, as raízes da equação são 7 e 1.
delta = b²-4ac
delta = (-8)² - 4 x 1 x 7
delta = 64 - 28
delta = 36
raiz de delta = 6
substituindo na fórmula de báskara: x = 8 + 6 / 2 ou x = 8 - 6 / 2
então, as raízes da equação são 7 e 1.
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás